ANALISIS DAMPAK KENAIKAN HARGA KEDELAI TERHADAP PENDAPATAN USAHA PENGERAJIN TEMPE” DI DESA NDIWAR KECAMATAN LELAK KABUPATEN MANGGARAI TENGAH - Nur Aslindawaty; Rista Ani Cembes (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This study aims to determine the impact of the increase in soybean prices on the business income of tempe craftsmen in Ndiwar Village, Lelak District, Central Manggarai Regency. The type in this research is qualitative. Researchers in qualitative research are people who examine and explore the entire space carefully, orderly and freely, and some even call it a Key Instrument. The results of the study on the analysis of the impact of the increase in soybean prices on the business income of tempe craftsmen in Ndiwar Village, Lelak District, Central Manggari Regency. small, mostly using family labor, and the marketing reach is still small and the increase in soybean prices which reached 92.94 percent greatly affected the business of tempeh craftsmen because the high price of soybeans, limited capital and declining demand for tempeh made the business conditions of tempe craftsmen change the production cycle , a decrease in production volume, a decrease in the use of input factors, an increase in selling prices, a decrease in revenue and a decrease in operating income.